Bioactive potential of actinobacteria against drug resistant pathogens - Pazhanimurugan R., V. Gopikrishnan, T. Shanmuga Sundaram, M. Radhakrishnan, R. Balagurunathan (Journal of Applied Pharmaceutical Science)
The present investigation was focused to study the antagonistic potential of actinobacterial strain TK2 isolated from Thirukurungudi Hills (Western Ghats, Tamil Nadu), against selected drug resistant bacterial pathogens. Of the 9 clinical bacterial strains, S. aureus was found to be resistant against methicillin and vancomycin while the remaining 8 gram negative pathogens were confirmed as extended spectrum beta lactamase (ESBL) producers. Strain TK2 showed good antagonistic activity against all the bacterial pathogens, except the three isolates of P. aeruginosa. Strain TK2 produced the antimicrobial activity on 4th day of incubation when growing on ISP2 agar medium whereas the same strain showed activity only on 8th day of incubation when it was grown on ISP2 broth. Of the various solvents tested for extraction, bioactive compound was extracted only in ethyl acetate. The crude extract showed 14-18 mm inhibition zone in disc diffusion method. The crude extract produced two spots in thin layer chromatography (TLC) in chloroform: methanol (30:60) solvent system. In bioautography, the second spot (Rf value 0.685) showed activity. The active compound was purified by preparative TLC, which showed maximum activity (15-20 mm inhibition) against test pathogens. Based on the results of chemical screening, the active compound was identified as sugar containing substance. Strain TK2 showed good growth on various growth media and culture conditions. Based on the studied phenotypic characteristics strain TK2 was identified as the species of the genus Streptomyces. Of the various growth parameters tested, ISP2 medium, glucose, pH 7, 1% NaCl and temperature 300C was influenced the antagonistic activity of strain TK2. Strain TK2 will be a potential for the isolation of bioactive compound(s) which will be a candidate for the development of antibiotic against drug resistant bacterial pathogens.
Keywords: Antagonistic activity, resistant pathogens, optimization, taxonomy, actinobacteria.